Anti-hangover and anti-hypertensive effects in vitro of fermented persimmon juice - Chang Zhou; Jiao Li; Kemin Mao; Jie Gao; Xiyu Li; Tongxin Zhi; Yaxin Sang (CyTA - Journal of Food, 2019)
This study aimed to develop and characterize a fermented persimmon juice with potential anti-hangover and anti-hypertensive effects using gamma-aminobutyric acid (GABA)-producing lactic acid bacteria. Results showed the co-fermentation of Lactobacillus plantarum C17 and Lactobacillus pentosus Lp-B produced the highest yield of 2.102 mmol/L of GABA. After 48 h of fermentation, GABA was produced at the conversion rate of 69.32% from glutamate. The alcohol dehydrogenase activation rate, acetaldehyde dehydrogenase activation activity and hydroxyl inhibition rate of fermented persimmon juice were 38.91%, 34.72%, and 16.79%, respectively, which displayed higher anti-hangover activity compared to unfermented persimmon. Moreover, the angiotensin-converting enzyme inhibition ability of fermented persimmon juice was 42.34% and the expression level of human endothelin-1 was reduced to 34.64 μg/mL. These findings indicated GABA-enriched fermented persimmon juice had potential anti-hangover and anti-hypertensive properties.